Government agencies overseeing municipal council funds - Al- marazqah, Abdullah Atallah Gibeal (Journal of Economic, Administrative and Legal Sciences, 2021)
The research aims to identify the main internal and external monetary supplies to municipalities and their role in turning municipalities to development institutions. IN addition, this research identified the main supervision practices over the municipal councils, which are carried out by some government agencies. The effect of such practices on the adequacy of work has also been identified. the descriptive approach has been used to handle these monetary supplies based on the legislations and regulations that are related to them. the analytical approach has also been employed by analyzing some legal provisions that are related to the research.In conclusion, after having handled the surveillance of the government agencies over municipal councils funds. It is essential to show the main results that we concluded as well as stating some recommendations, which are five.Among the most important results of the study: The financial autonomy that municipalities have is not absolute and relative, which emphasizes the idea that municipalities funds are subject to control by the central authority. this can sometimes lead to imposing some restrains on the jurisdiction of the municipal councils.The study recommended Increasing the financial autonomy of the municipalities as imposing censorship over the financial autonomy may be a cause of shortage of funds.
Keywords: oversight; government agencies; municipal councils